Tobacco Farm Workers' Incomes: Analyzing the Influence of Diverse Socio-Economic Factors - Tamalia Azzahra Wahyuningtyas; suswadi; Irawan, Norbertus Citra (Journal of Rural and Urban Community Studies, 2025)
Understanding the socio-economic factors influencing tobacco farm laborers’ income is essential for improving their financial stability and productivity. Many farm workers face economic uncertainty due to low education levels, limited experience, and fluctuating wages. Existing studies often overlook the combined impact of these factors, creating a research gap in labor income dynamics. This study aims to analyze how education, experience, age, and family size affect farm laborers' earnings. A quantitative descriptive method was employed, using surveys, interviews, and multiple linear regression analysis on respondents from Kagokan and Klaseman villages, Gatak District. The findings reveal that education and experience positively impact income, while age negatively influences earnings due to declining physical ability. Family size shows no significant effect. These results highlight the need for policy interventions such as vocational training, wage restructuring, and education access for farm laborers. Policymakers should implement sustainable programs to bridge economic disparities and enhance workforce efficiency. Future research should explore the role of agricultural technology adoption and gender-based income disparities, offering deeper insights into labor market dynamics.